Managing negative word-of-mouth: the interplay between locus of causality and social presence. Issue 2 (19th December 2019) - He, Yi; Ju, Ilyoung; Chen, Qimei; Alden, Dana L.; Zhu, Hong; Xi, Kaiyuan
Abstract : Purpose: This paper aims to describe the results of four studies that examine the interaction effects between locus of causality and social presence on consumers' emotional response to a service failure and how they subsequently cope with the negative emotional experiences through support-seeking or vindictive negative word-of-mouth (NWOM). Design/methodology/approach: To evaluate the research hypotheses, one online content analysis study and three experiments were conducted. Findings: The results of the four studies show that when locus of causality information is not available (Studies 1 and 2), consumers are more likely to engage in support-seeking NWOM when there is social presence (versus no social presence). When a service failure is externally/internally attributed, social presence leads to less/more vindictive NWOM (Studies 3 and 4). The results clarify the underlying affective processes (frustration, anger and embarrassment) that account for the unique interaction effects involving locus of causality and social presence on NWOM. Originality/value: Despite promising progress in both social presence and service failure research, scholarly attempts aiming to draw the theoretical linkages between these two streams are relatively scarce, and it remains unknown regarding whether and how social presence influences NWOM in the event of service failure. Against this backdrop, this research examines the effects of social presence on consumer NWOM in service failure. The authors further contribute to both research streams by testing the effects of an important set of emotions as mediators, as well by exploring the conditions under which a particular emotion is more predictive of its corresponding outcomes. These findings offer important insights that help service managers effectively mitigate customer NWOM at the point of service delivery.